PERAN KEPERCAYAAN DALAM MEDIASI FAKTOR YANG MEMPENGARUHI MINAT MENGGUNAKAN LINKAJA SYARIAH - Paryono, Paryono; Hana, Kharis Fadlullah (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2025)
This study aims to investigate of usability, convenience, security and service features as factors on the interest in using the LinkAja Syariah e-wallet mediated by trust. Rapid technological developments have resulted in the growth of new innovations such as digital wallets. Indonesia is a country with the highest digital wallet users. This study involved the people of Kudus City who use the LinkAja Syariah e-wallet. The method used in this study is a quantitative approach. The data collection process used a questionnaire and data analysis techniques using the SmartPLS3 application. The research findings show that the independent variables of usability, convenience, security and service features have a positive effect on interest in using. Then trust also has a direct positive effect on interest in using. The results of hypothesis testing do not directly show the role of trust as a mediator of usability, convenience, security and service features have a positive effect on interest in using. This study provides an overview that the people of Kudus City use the LinkAja Syariah e-wallet influenced by usability, convenience, security and service features with high trust.